2017
DOI: 10.1186/s40317-017-0137-8
|View full text |Cite
|
Sign up to set email alerts
|

Pop-up satellite archival tag (PSAT) temporal data resolution affects interpretations of spawning behaviour of a commercially important teleost

Abstract: Background:The effects of temporal data resolution on the interpretation of fish behaviours are questions fundamental to research programs using electronic tags with finite data storage and data transmission capacities. However, understanding these effects requires sub-sampling high-resolution data at multiple temporal resolutions. In pop-up satellite archival tags (PSATs), data transmissions via satellite are limited, so temporal resolution is a decreasing function of the deployment duration. Physical recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Such consistency is surprising given that rates of missing daily data were high (64%–93%) because PSATs were recovered a few days after release, which prevented more complete data transmission. With lower rates of missing data such as the one around 39% observed in our previous tagging efforts (Fisher et al., 2017; Le Bris et al., 2018; Murphy et al., 2017), we suspect that geolocation will be even less affected. Braun, Galuardi, et al.…”
Section: Discussionmentioning
confidence: 76%
“…Such consistency is surprising given that rates of missing daily data were high (64%–93%) because PSATs were recovered a few days after release, which prevented more complete data transmission. With lower rates of missing data such as the one around 39% observed in our previous tagging efforts (Fisher et al., 2017; Le Bris et al., 2018; Murphy et al., 2017), we suspect that geolocation will be even less affected. Braun, Galuardi, et al.…”
Section: Discussionmentioning
confidence: 76%
“…Electronic tagging studies characterize detailed movement of individuals, and even more detailed if archival tags are retrieved and allow for analysis at higher temporal resolution (Fisher et al 2017), allowing insight into fine-scale behavior. Progress in the last decade in electronic tagging technologies has revealed a variety of migratory behaviors through the reconstruction of migration tracks using geolocation models (Seitz et al 2017;Le Bris et al 2018;Liu et al 2019;Gatti et al 2020;James et al 2020;Gatti et al 2021).…”
Section: Movement and Migrationmentioning
confidence: 99%
“…The advent of electronic archival tags has offered new opportunities to identify putative spawning behavior from the recorded high-resolution depth times series (Fisher et al 2017), from which distinct spawning rises can be detected (Murphy et al 2017;Le Bris et al 2018). Early utilization of PSATs on Atlantic halibut revealed that fish on the Grand Banks and south of Newfoundland spawn at depths of 450-1050 m from October through February (Armsworthy et al 2014), most likely on the continental slope.…”
Section: Spawning Behaviormentioning
confidence: 99%
See 2 more Smart Citations